Extracellular Methionine Production by Submerged Fermentation in Shake Flasks using Bacteria Isolated From the Soil - Jude , Okpalla (African Journal of Education,Science and Technology (AJEST), 2016)
Extracellular methionine production by submerged fermentation using bacteria isolated from the soil was studied. Soil samples were collected from a depth of 5cm at different locations within Ihiala town in Ihiala LGA Anambra State. Each sample suspension was inoculated into plates of nutrient agar and tryptone soy agar using standard procedure. The bacteria isolated were screened for methionine production on solid minimal medium already inoculated with methionine auxotroph Escherichia coli. Qualitative observation of the plates for halo growth of the E.coli revealed the active methionine producers. The best producers were selected and employed in methionine production by submerged fermentation. A total of 87 isolates were screened for extracellular methionine production and eighteen of the isolates were found to be methionine producers, with isolates FZ13, ZM10 and ZM22 selected as the best producers. The selected isolates were characterize and identified as Bacillus species. Submerged methionine production for FZ13 and ZM22 increased with time and was highest at 72h (1.90 and 1.26 mg/ml).The growth of both isolates was maximum also at the same period , while the residual sugar gradually decreased throughout the fermentation period. For isolate ZM10 maximum methionine production was observed after 96h (1.63mg/ml), while the highest growth was recorded at 72h.The residual sugar decreased till the end of fermentation. The result showed that methionine producing bacteria abound in the soil.